Efektivitas Kebijakan Bebas Peredaran Uang (BPU) Dalam Mencegah Peredaran Narkotika Berdasarkan Pasal 5c Permenkumham No. 29 Tahun 2017 di Lembaga Pemasyarakatan Narkotika Kelas IIB Muara Sabak - Azed, Abdul Bari; Abdullah, Muhammad Zen; Rahman, Juni (Universitas Batanghari Jambi, 2023)
Since the establishment of Correctional Institutions (Lapas), which were originally called prisons and State Detention Centers, various regulations regarding money control in prisons and detention centers have been enforced. However, various efforts that have been made through the application of regulations and restrictions as well as policies on free circulation of money in prisons/detention centers are still not in accordance with the expected objectives. The purpose of this study is to understand and analyze the effectiveness of the Free Money Circulation policy in preventing the circulation of narcotics based on Article 5C of Permenkumham No. 29 of 2017 at the Muara Sabak Class IIB Narcotics Penitentiary, to analyze the inhibiting factors, as well as efforts to overcome them. The method used in this research is empirical juridical which uses primary data. The results of the research show that the policy of free circulation of money based on Article 5C of Permenkumham No. 29 of 2017 is less effective in preventing the circulation of narcotics at Class IIB Narcotics Prison Muara Sabak. This is proven based on facts supported by data obtained in research, that from 2020 to 2022 the number of violations committed by WBP Class IIB Narcotics Prison Muara Sabak is still quite high. Factors inhibiting the effectiveness of the free circulation of money policy at the Muara Sabak Class IIB Narcotics Penitentiary consist of the difficulties experienced by the WBP and the WBP's family to adapt to the use of technology, limited supporting infrastructure that hinder the implementation of the free circulation of money policy at the Muara Sabak Class IIB Narcotics Penitentiary, and there are still gaps related to the entry of cash into prisons, namely related to the accuracy and integrity of officers related to searches of people and goods. Efforts to overcome these obstacles, among others, officers should be more active socialization related to the implementation of the policy of free circulation of money at Class IIB Narcotics Lapas Muara Sabak to WBP and their families which is carried out on an ongoing basis, seeking to prepare supporting facilities/infrastructure either through budget allocations for prisons or through collaboration with other parties. external, and Instilling the values of integrity and professionalism by leaders both at the administrator level and at the supervisory level to all officers.